The relationship between audit client satisfaction and audit quality attributes: case of Malaysian listed companies - Mohd Iskandar, Takiah; Rahmat, Mohd Mohid; Ismail, Hashanah (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
This study examines client satisfaction over audit services as perceived by the company management and its relationships with audit quality attributes. Comparisons of audit client satisfaction are made between Big 4 and non-Big 4 firms on the audit of Bursa Malaysia listed companies. The study employs the Behn et al. (1997) research instrument consisting of fifteen item questionnaires of audit quality attributes and two items of client satisfaction of audit performance at the firm and team levels. The questionnaire solicits perceptions of financial controllers over the quality attributes of auditors and their level of satisfactions with audit services. Results show that quality attributes of audit firm are ranked higher than quality attributes of audit team. There is no significant difference in client satisfaction over the performance of audit between the Big 4 and non-Big 4. Further analysis shows that client satisfaction is significantly related to four audit firm quality attributes, i.e. prior experience, responsiveness, independence, and commitment of audit firm to quality audit. Results also show that client satisfaction is significantly related to certain quality attributes of audit team, i.e. experience with client, independence, involvement in the engagement, conduct of field works, and ethical and knowledgeable of accounting and auditing standards.